Numerical Analysis of a Real Photovoltaic Module with Various Parameters. (20th March 2018) - Nituca, Costica; Chiriac, Gabriel; Cuciureanu, Dumitru; Zhang, Guoqiang; Han, Dong; Plesca, Adrian
Abstract : This article presents a real photovoltaic module with modeling and simulations starting from the model of a photovoltaic (PV) cell.I - V, P - V, andP - I characteristics are simulated for different solar irradiation, temperatures, series resistances, and parallel resistances. For a real photovoltaic module (ALTIUS Module AFP-235W) there are estimated series and parallel resistances for which the energetical performances of the module have optimal values for a solar radiation of 1000 W/m 2 and a temperature of the environment of 25°C. Temperature influence over the PV module performances is analyzed by using a thermal model of the ALTIUS Module AFP-235W using the finite element method. A temperature variation on the surface of the PV module is starting from a low value 40.15°C to a high value of 52.07°C. Current and power estimation are within the errors from 1.55% to about 4.3%. Experimental data are measured for the photovoltaic ALTIUS Module AFP-235W for an entire daylight.